Pemanfaatan Kulit Jeruk Nipis (Citrus aurantifolia) Menjadi Handsanitizer Gel - Nur Mu’min; Mirnawati; Muhammad Yunus (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2021)
Hand sanitizer is a hand sanitizer antiseptic that is able to clean germs or viruses that stick to the hands. Most in the hand sanitizer market still use alcohol with a concentration of ±50%-70%. The use of alcohol in hand sanitizer is considered less safe for health because alcohol is an organic solvent that can dissolve the layer of fat and sebum on the skin that serves as a protector against infection of microorganisms. In addition, alcohol is also flammable and if repeated use on the hands will cause irritation. Research methods conducted in the determination of water content, the manufacture of hand sanitizer gel, pH measurement, viscosity and antimicrobials. Variations in carbpol concentration affect the physical properties and physical stability of the gel. Increased concentration of Carbpol increases the viscosity of the preparation. Based on the results of research conducted, it can be concluded that lime (Citrus aurantifolia) has the potential to inhibit the growth of microbes <1,0 x 101 colonies / g.